Specificity of training and its relation to the performance of distance runners - Hewson, D. J.; Hopkins, W. G. (International Journal of Sports Medicine, 1996)
Valid 6-month retrospective questionnaires were completed by distance runners (M = 234, F = 119) who performed events from 800 m to marathons. The major finding was a weak but significant relationship between performance and seasonal mean weekly duration of moderate continuous running for long-distance specialists. It was also found that there were weak negative relationships between seasonal mean relative training paces of moderate and hard continuous running. The size of the correlations was small with the largest accounting for 16% of variance. The training of better runners is not characterized strongly by significant specificity. Implication: Given the complexity of training for developing both general (base) capacities and specific capacities it is not surprising that single factors do not relate to performances. Training effects are multivariate and unless they are considered as a package, true relationships of value will not be revealed.